2013
DOI: 10.5936/csbj.201304005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Nanotechnology in Cardiovascular and Pulmonary Regeneration

Abstract: Recently, a wide range of nanotechnologies has been approached for material modification by realizing the fact that the extracellular matrix (ECM) consists of nanoscale components and exhibits nanoscale architectures. Moreover, cell-cell and cell- ECM interactions actively occur on the nanoscale and ultimately play large roles in determining cell fate in tissue engineering. Nanomaterials have provided the potential to preferentially control the behavior and differentiation of cells. The present paper reviews t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The goal of regenerative medicine, particularly tissue engineering, is to create a natural tissue to replace a damaged body part. Currently, nanotechnology is being used to see how the spatiotemporal profile of the ECM that regulates cellular behaviors can be adequately controlled [ 236 ]. Most human cells have their sizes in the microscale range (10–100 μ m); however, the ECM that plays the crucial role in almost all cellular functions is in the order of the nanoscales [ 236 ].…”
Section: Pulmonary System and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of regenerative medicine, particularly tissue engineering, is to create a natural tissue to replace a damaged body part. Currently, nanotechnology is being used to see how the spatiotemporal profile of the ECM that regulates cellular behaviors can be adequately controlled [ 236 ]. Most human cells have their sizes in the microscale range (10–100 μ m); however, the ECM that plays the crucial role in almost all cellular functions is in the order of the nanoscales [ 236 ].…”
Section: Pulmonary System and Diseasesmentioning
confidence: 99%
“…Currently, nanotechnology is being used to see how the spatiotemporal profile of the ECM that regulates cellular behaviors can be adequately controlled [ 236 ]. Most human cells have their sizes in the microscale range (10–100 μ m); however, the ECM that plays the crucial role in almost all cellular functions is in the order of the nanoscales [ 236 ]. Recreating the ECM of the lung tissue at the nanoscale has been a daunting task due to the highly complex ECM of the lung tissue, hence the move towards the decellularization of donor human or animal lung tissue as a scaffold and then recellularizing it with the required (stem) cells.…”
Section: Pulmonary System and Diseasesmentioning
confidence: 99%
“…Tissue-engineered successful vascular grafts should have mechanical strength for the prevention of surface thrombosis, and highly organized structures combining with ECM proteins. It seems that biomaterial surface modification on the nanoscale enhances vascularization in tissue-engineered constructs by influencing cell alignment, adhesion, and differentiation [ 64 66 ]. A study regarding the use of collagen-like synthetic self-assembling nanofiber hydrogels successfully supported the culture of both neonatal rat cardiomyocytes and human embryonic stem cell-derived cardiomyocytes [ 67 ].…”
Section: Applications Of Nanostructured Materials In Tementioning
confidence: 99%
“…Various studies demonstrated that scaffolds provided not only a suitable mechanical support to cell culture, but they can also regulate SC behaviour by favouring SC survival, proliferation and differentiation, and providing a guide for tridimensional (3D) tissue reconstruction [ 9 , 10 , 11 ]. In fact, various studies showed that differentiation occurred either in the presence [ 12 , 13 , 14 , 15 , 16 ] or in the absence [ 9 , 17 , 18 , 19 ] of external stimuli when SCs have been cultured on biomaterials.…”
Section: Introduction: Clinical Needmentioning
confidence: 99%